Continuous Apical Negative-Pressure Ultrasonic Irrigation (CANUI): A new concept for activating irrigants - Castelo-Baz, Pablo (J Clin Exp Dent, 2017)
Background: Irrigation of the root canal system is an essential step in the endodontic treatment. The aim of this article is to introduce continuous apical negative-pressure ultrasonic irrigation (CANUI), a new irrigation concept, and compare the characteristics of this new technique with current devices for activating the irrigant. Material and Methods: CANUI is designed for cleaning and disinfecting the root canal system. The device consists of a tube inside another tube that allows the continuous ultrasonic exchange of fresh irrigant, as the irrigant is simultaneously aspirated apically. The coronal and apical tubes are 0.75 and 0.3 mm in diameter, respectively. It is composed of a nickel-titanium microcannula suitable for the working length of curved canals. Results: The CANUI technique has the advantages of apical negative pressure (to avoid apical extrusion of the irrigant) and continuous ultrasonic irrigation (continuous refreshment of the irrigant and forced introduction into the canal ramifications). Conclusions: The CANUI technique could improve the irrigation technique of dentists to reach more disinfection in endodontic treatments. Key words:Apical negative pressure, continuous ultrasonic irrigation, irrigation in curved canals, irrigation systems.